2010
DOI: 10.1210/jc.2010-0766
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography: A New Ultrasound Imaging Mode for the Differential Diagnosis of Benign and Malignant Thyroid Nodules

Abstract: Promising results have been obtained with SWE. This technique may be applied to multinodular goiters. Larger prospective studies are needed to confirm these results and to define the respective places of SWE, US, and FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
314
4
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(348 citation statements)
references
References 31 publications
12
314
4
13
Order By: Relevance
“…Liu et al [13] also reported that E mean ≥ 38.3 kPa was the most useful predictor among all SWE indices in differentiating benign and malignant thyroid nodule. In the present study, the optimal cut-off for E maximum and E mean for distinguishing benign and malignant nodules were 67.3 and 23.1 kPa, respectively, which were consistent with the result of previous reports in E maximum [15,36]. In our study, there was no significant difference in the E minimum of benign and malignant nodules, which was different from previous studies [13,33,34].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Liu et al [13] also reported that E mean ≥ 38.3 kPa was the most useful predictor among all SWE indices in differentiating benign and malignant thyroid nodule. In the present study, the optimal cut-off for E maximum and E mean for distinguishing benign and malignant nodules were 67.3 and 23.1 kPa, respectively, which were consistent with the result of previous reports in E maximum [15,36]. In our study, there was no significant difference in the E minimum of benign and malignant nodules, which was different from previous studies [13,33,34].…”
Section: Discussionsupporting
confidence: 89%
“…However, Bhatia et al [35] found that E mean of 34.5 kPa or higher was a significant predictor of malignancy with a sensitivity of 52.9% and specificity of 77.8%. Other studies suggested that SWE was useful in differentiating benign and malignant thyroid nodules when the cut-off level of 66 kPa and 65 kPa for E maximum were used, respectively [15,36]. However, Szczepanek-Parulska et al [37] found that the threshold value of 50 kPa for E maximum was the most useful SWE parameter in the differentiation of benign and malignant nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Park et al (24) demonstrated a high interobserver variability of the qualitative methods of elastographic evaluation, where the elasticity image and score depended on the extent of tissue compression. On the other hand, since the technique of Shear Wave Elastography used in our study is devoid of the need for freehand external compression, it can be assumed to be operator independent, reproducible, and objective in the evaluation of tissue firmness (25).…”
Section: Discussionmentioning
confidence: 99%
“…Sebag et al investigated the efficiency of SWE in predicting malignancy in solitary or multiple thyroid nodules. Using a cut-off level of 65 kPa, they could predict malignancy with sensitivity of 85.2%, specificity of 93.9% and positive predictive value (PPV) of 92.3% [32].…”
Section: Malignant Thyroid Nodulesmentioning
confidence: 99%